Completely supervised training algorithms for B-spline neural networks and neuro-fuzzy systems - Ruano, Antonio (2013)
Complete supervised training algorithms for B-spline neural networks and fuzzy rule-based systems are discussed. By interducing the relationship between B-spline neural networks and certain types of fuzzy models, training algorithms developed initially for neural networks can be adapted by fuzzy systems.